2001
DOI: 10.1159/000051669
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Plaques and Linear Pigmentation in Adult-Onset Still’s Disease

Abstract: A 25-year-old Japanese man presented with high spiking fever, arthralgia and a skin rash. A pruritic edematous erythema with persistent plaques was found mainly on the trunk; these lesions persisted even when the fever subsided, with prominent linear pigmentation. As marked neutrophilia and a high level of serum ferritin were detected, a diagnosis of adult-onset Still’s disease (AOSD) was made, even though the persistent eruption was not characteristic of the disease. Oral prednisolone, together with low-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 6 publications
7
55
1
Order By: Relevance
“…This variant manifests as nonevanescent pruritic erythematous papules and plaques with slight scale that often presents with a flagellate erythemalike presentation with linear configurations on the trunk and extremities. [4][5][6][7][8] The linearity may represent a Koebner phenomenon or scratching because the eruption characteristically spares the mid-back. Differential diagnosis of flagellate erythema includes bleomycin, dermatomyositis, and shiitake mushroom dermatitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This variant manifests as nonevanescent pruritic erythematous papules and plaques with slight scale that often presents with a flagellate erythemalike presentation with linear configurations on the trunk and extremities. [4][5][6][7][8] The linearity may represent a Koebner phenomenon or scratching because the eruption characteristically spares the mid-back. Differential diagnosis of flagellate erythema includes bleomycin, dermatomyositis, and shiitake mushroom dermatitis.…”
mentioning
confidence: 99%
“…9 This nonclassic variant also has unique histopathologic features including dyskeratosis in the upper layers of the epidermis extending into the stratum corneum without involvement of the basal layer and a superficial dermal infiltrate with neutrophils and lymphocytes. [4][5][6][7][8] While this nontypical variant was first described by Kaur et al 4 in 1994, it may be an underrecognized cutaneous manifestation of AOSD. In the largest case series of persistent pruritic papules and plaques published to date, Lee et al 6 found that 65% (11 of 17) of their patients with AOSD had this variant.…”
mentioning
confidence: 99%
“…However, recent findings show that not only typical evanescent rash but also various skin lesions are associated in AOSD [11][12][13][14][15] . The representative characteristic skin lesion among the non-classical skin rash is called persistent pruritic papules and plaques which presents erythematous, slightly scaly papules with linear configuration on the trunk and proximal extremities [12] . Other non-classical skin lesions include urticarial [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Other non-classical skin lesions include urticarial [13] . Interestingly, persistent pruritic papules and plaques show unique histological features such as peculiar, distinctive distribution of dyskeratotic keratinocytes in the cornified layers as well as in the epidermis [12,14] . Our dermatologist diagnosed her cutaneous symptom as toxicoderma at the initial presentation which was improved by the prednisolone administration.…”
Section: Discussionmentioning
confidence: 99%
“…Soy 23 Erythema chronicum migrans Saito et al 24 Persistent plaques and linear pigmentation Suzuki et al 25 Non-caseating dermal granulomas…”
Section: Angioedemamentioning
confidence: 99%